2003
DOI: 10.1067/mva.2003.212
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm size regression after endovascular repair is endograft dependent

Abstract: Long-term morphologic changes after endovascular aneurysm repair depend on endograft type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 32 publications
2
85
0
Order By: Relevance
“…Changes in aneurysm diameter remain an important marker of aneurysm exclusion, and device-specific dif- van ferences have been reported. 13,26,28,29 Certain stent-graft makes (e.g., Zenith) are associated with shrinkage more than others. The persistence of differences after risk adjustment (e.g., for endoleak) in this study might suggest an additional role for device components, such as fabric, in influencing postoperative changes in aneurysm size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in aneurysm diameter remain an important marker of aneurysm exclusion, and device-specific dif- van ferences have been reported. 13,26,28,29 Certain stent-graft makes (e.g., Zenith) are associated with shrinkage more than others. The persistence of differences after risk adjustment (e.g., for endoleak) in this study might suggest an additional role for device components, such as fabric, in influencing postoperative changes in aneurysm size.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive changes in arterial anatomy during follow-up, such as neck dilatation or aneurysmal transformation of iliac landing zones, may compromise stent-graft function later on. 14,15,24,[28][29][30] Physician-related factors, such as diagnostic insight, judgment of suitability for treatment, and operating experience, also influence outcome. 31 All of these factors have been constantly changing as endovascular repair has evolved, creating a potential confounding effect upon comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two current methods used to treat AAAs are (a) open surgical repair by replacing the diseased segment with a synthetic arterial graft or (b) endovascular repair by deploying a stent that is designed to shield the aneurysmal wall from the hemodynamic loads. Particularly provocative is the observation that some endovascularly treated AAAs actually regress, with decreases in size up to 8% (194,195). Given that an AAA actively grows and remodels during most of its natural history, this suggests that a stent can alter the applied loads in such a way that G&R may reverse the natural course of enlargement, which usually ends in rupture.…”
Section: Closurementioning
confidence: 99%
“…Abdominal aortic size regression after endovascular repair depended on the type of endograft. 13,14 A dense intraluminal thrombus may prevent a rapid regression of the AAA; however, several authors reported that the rate of change was unrelated to the amount of preoperative thrombus within in. 3,15 In untreated aneurysms, the individual expansion rate is unpredictable while the mean expansion rate has been documented.…”
Section: Discussionmentioning
confidence: 94%